ICT in Education of Architects. How to Strike a Balance?. (21st February 2017) - Gushchin, Alexander; Divakova, Marina
Abstract: The paper is devoted to the issue of finding a balance in the use of ICT for training architects and, more broadly, other creative professionals. On the one hand, the introduction of ICT has raised a wave of euphoria and brought about such phenomena as e-learning and massive open courses. On the other hand, the teaching of architecture rests on the long-established pedagogical tradition connected with free-hand drawing and mockup making, i.e. activities that are hard to learn with the help of computer.